Protective role of miR-23b-3p in kainic acid-induced seizure. Issue 10 (6th July 2016) - Zhan, Lianbo; Yao, Yi; Fu, Huajun; Li, Zhenghui; Wang, Fengpeng; Zhang, Xiaobin; He, Wencan; Zheng, Weihong; Zhang, Yunwu; Zheng, Honghua
Abstract : Dysregulation of microRNAs has been proposed to contribute toward epilepsy. The miRNA miR-23b-3p has been found to protect against neuronal apoptosis and the production of reactive oxygen species. In this study, we assessed the potential role of miR-23b-3p in the kainic acid (KA)-induced seizure model. We found that miR-23b-3p levels were significantly decreased in the brain cortex of mice and in cultured mouse primary neurons treated with KA. Importantly, supplement of miR-23b-3p agomir by an intacerebroventricular injection alleviated seizure behaviors and abnormal cortical electroencephalogram recordings in KA-treated mice. Together, these results indicate that miR-23b-3p plays a crucial role in suppressing seizure formation in experimental models of epilepsy and that miR-23b-3p supplement may be a potential anabolic strategy for ameliorating seizure.